Mechanistic Study of the Activation and the Electrocatalytic Reduction of Hydrogen Peroxide by Cu‐tmpa in Neutral Aqueous Solution. Issue 15 (28th May 2021) - Langerman, Michiel; Hetterscheid, Dennis G. H.
Abstract: Hydrogen peroxide plays an important role as an intermediate and product in the reduction of dioxygen by copper enzymes and mononuclear copper complexes. The copper(II) tris(2‐pyridylmethyl)amine complex (Cu‐tmpa) has been shown to produce H2 O2 as an intermediate during the electrochemical 4‐electron reduction of O2 . We investigated the electrochemical hydrogen peroxide reduction reaction (HPRR) by Cu‐tmpa in a neutral aqueous solution. The catalytic rate constant of the reaction was shown to be one order of magnitude lower than the reduction of dioxygen. A significant solvent kinetic isotope effect (KIE) of 1.4 to 1.7 was determined for the reduction of H2 O2, pointing to a Fenton‐like reaction pathway as the likely catalytic mechanism, involving a single copper site that produces an intermediate copper(II) hydroxo species and a free hydroxyl radical anion in the process. Abstract : Neutral territory : The electrochemical reduction of hydrogen peroxide was studied in presence of Cu‐tmpa. Our combined mechanistic studies including solvent kinetic isotope effects (KIE), rate orders, and catalytic rate constants show that hydrogen peroxide is most likely activated by copper(I) via a Fenton‐like mechanism wherein hydroxyl radicals are formed.